2012
DOI: 10.5005/jp-journals-10024-1168
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Colonization and their Relation with Potential Cofactors in Patients with Denture Stomatitis

Abstract: Aim To determine microbial prevalence in the mucous membrane and prosthesis of denture wearers with and without denture stomatitis and to study its relationship with potential clinical cofactors. Materials and methods Saliva was collected from 200 patients (100 female and 100 male) wearing dental prosthesis for measurement of pH. Oral samples of the mucous membrane and of dentures were taken with sterile swab for microbiological analysis. Medical and dietary history of the subjects was recorded. Chi-square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In such studies, C. albicans is reported as being the most prevalent Candida species on the dentures of stomatitis patients, with an incidence of 54-75%, and a lower incidence evident on the dentures on non DS patients (39%) [28][29][30]. In the present study, similar findings were reported, with a 57% incidence of oral colonisation by C. albicans in DS patients and a 22% incidence in non-DS patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In such studies, C. albicans is reported as being the most prevalent Candida species on the dentures of stomatitis patients, with an incidence of 54-75%, and a lower incidence evident on the dentures on non DS patients (39%) [28][29][30]. In the present study, similar findings were reported, with a 57% incidence of oral colonisation by C. albicans in DS patients and a 22% incidence in non-DS patients.…”
Section: Discussionsupporting
confidence: 87%
“…A number of previous investigations have examined the microbiology of DS, particularly with respect to the Candida species colonisation of the oral cavity [28][29][30]. In such studies, C. albicans is reported as being the most prevalent Candida species on the dentures of stomatitis patients, with an incidence of 54-75%, and a lower incidence evident on the dentures on non DS patients (39%) [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several pathologies and their treatments can increase a patient’s exposure to C. albicans infection [ 156 ]. Frequently the atrophic aspect of denture stomatitis appears to be related to a general pathology such as diabetes and hypertension [ 157 ].…”
Section: Neutrophils and Denture-related Candida Stomatitismentioning
confidence: 99%
“…S.aureus is now an accepted member of the normal oral flora and has been detected in conjunction with C.albicans in the oral cavity, and is thought to be associated with DS . [10][11][12] More recently, small colony variants of S.aureus were found to associate with C.albicans amongst denture wearers. 13 Elsewhere, S.aureus infections range from superficial, localised wound infections to systemic sepsis, all of which are dependent on a portal of entry through the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%